2021
DOI: 10.3390/molecules26185580
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Phenolics, Sterols, and Terpenes in Colored Wheat Grains by Liquid Chromatography with Tandem Mass Spectrometry

Abstract: The colored grain of wheat (Triticum aestivum L.) contains a large number of polyphenolic compounds that are biologically active ingredients. The purpose of this work was a comparative metabolomic study of extracts from anthocyaninless (control), blue, and deep purple (referred to here as black) grains of seven genetically related wheat lines developed for the grain anthocyanin pigmentation trait. To identify target analytes in ethanol extracts, high-performance liquid chromatography was used in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
1
5
0
Order By: Relevance
“…This may be due to the transferred chromosomal segments of Thinopyrum ponticum in blue-grained wheats having a different length and position, resulting in great genetic diversity among individual blue grain genomes ( 8 ). The various studies above confirm previous findings or find contradictory results, which may be due in part to different genotypes and growing sites resulting in unique chemical characteristics and specific compounds for each anthocyanin-rich strain ( 38 ).…”
Section: Discussionsupporting
confidence: 69%
“…This may be due to the transferred chromosomal segments of Thinopyrum ponticum in blue-grained wheats having a different length and position, resulting in great genetic diversity among individual blue grain genomes ( 8 ). The various studies above confirm previous findings or find contradictory results, which may be due in part to different genotypes and growing sites resulting in unique chemical characteristics and specific compounds for each anthocyanin-rich strain ( 38 ).…”
Section: Discussionsupporting
confidence: 69%
“…Bread wheat genotypes obtained from Omsk State Agrarian University (Russian) were used in the study. For the first time under conditions of Western Siberia, the variety EF 22 and line Element 22-PurplePF (8) with a purple grain color, as well as the bluegrained wheat line Element_22-Blue4Th (10) (Figure 1), were obtained by crossing variety Element 22 with an anthocyanin biosynthesis gene donor. Variety EF 22 and line Element 22-PurplePF (8) are sister lines that were obtained by individual selections from the hybrid combination Element 22 *2/i:S29PF.…”
Section: Methodsmentioning
confidence: 99%
“…The content of phytochemicals is generally limited in white- or red-grained wheat varieties while they occur more consistently in the so-called pigmented/colored varieties [ 7 ]. The colored wheat provides nutritional products with higher flavonoids (e.g., anthocyanin), phenolic acids, carotenoids, and other compounds with antioxidant activities that are primarily located in the pericarp and aleurone layers [ 8 , 9 , 10 ]. Owing to the presence of these compounds and dietary fibers, colored wheats exhibit antioxidant properties that basically help in protecting against degenerative diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative metabolomic studies have shown that coloured‐grain wheat lines have significantly higher levels of various substances, including those in the carboxylic acid, sterol, anthocyanin, and flavone families, compared to unpigmented‐grain controls (Razgonova et al ., 2021). They stated 3–6 times increase in the level of constituents belonging to carboxylic acid family, 2–3 times from sterol family, 2–4 times from anthocyanin family, and 1.5–2.7 times from flavone family in comparison to the unpigmented‐grain.…”
Section: Wheat Metabolomicsmentioning
confidence: 99%